Ethnomedicinal plants used for the treatment of cuts and wounds by Kuruma tribes, Wayanadu districts of Kerala, India - Binu Thomas, Rajendran Arumugam, Aravindhan Veerasamy, Sivalingam Ramamoorthy (Asian Pac J Trop Biomed, 2014)
Objective: T o study the ethnomedicinal uses by the Kuruma tribals for discovering new drugs to cure cuts and wounds so as to provid the data scientifically evaluated. Methods: A survey was conducted during M ay 2008 – S eptember 2009 to collect information on medicinal plants used by the Kuruma tribes and queries were made on the various species of plants used regularly and occasionally to cure cuts and wounds. Results: T he present study includes information on 34 plant species belonging to 32 genera and 25 families used by Kuruma tribe of W ayanad district of K erala for the treatment of cuts and wounds. Conclusions: T he present study of the knowledge on the folklore uses of the medicinal plants